Análisis de estados financieros de un gobierno autónomo descentralizado parroquial de la provincia de El Oro del período 2024 - Espinoza Chalen, Karina Isabel (Machala : Universidad Técnica de Machala, 2025)
This degree project aims to analyze the financial statements of the Parish Decentralized Autonomous Government (GAD) of El Oro Province for the 2024 fiscal year. The research seeks to evaluate the efficiency of public resource management through a technical analysis of the financial reports issued by the entity, such as the Statement of Financial Position, Statement of Financial Performance, and Budget Execution Statement. Parish-level GADs face limitations in regulatory compliance, weak internal control systems, and a lack of adequately trained personnel, which affects transparency and the efficient use of the budget. In this context, financial analysis becomes a fundamental tool for identifying weaknesses and proposing corrective actions. The study is framed within a qualitative approach, under the positivist paradigm and deductive method. Document analysis and structured observation were used as data collection techniques. The unit of analysis consisted of the financial statements for the year 2024, with administrative and financial personnel as indirect participants. Key dimensions analyzed include patrimonial structure, budget execution, regulatory compliance, and spending efficiency. The findings reveal an increase in institutional equity due to donations and improvements in financial outcomes. However, under-execution of 15% in public works, budget deficits, and weaknesses in asset registration and traceability were also detected. It is recommended to strengthen internal control, improve the quality of financial information, and enhance budget planning. This study contributes to public financial management and serves as a foundation for future research in the field of local government accountability
El presente trabajo de titulación tiene como objetivo analizar los estados financieros del Gobierno Autónomo Descentralizado (GAD) Parroquial de la provincia de El Oro, correspondientes al ejercicio fiscal 2024. Esta investigación busca evaluar la eficiencia en la gestión de los recursos públicos mediante el análisis técnico de los informes financieros emitidos, como el Estado de Situación Financiera, el Estado de Rendimiento Financiero y el Estado de Ejecución Presupuestaria. Los GAD parroquiales enfrentan limitaciones en el cumplimiento normativo, control interno débil y escaso personal capacitado, lo que afecta la transparencia y el uso eficiente del presupuesto. En este contexto, el análisis financiero permite identificar debilidades y proponer acciones correctivas. El estudio se enmarca en un enfoque cualitativo, con paradigma positivista y método deductivo. Se utilizó análisis documental y observación estructurada. La unidad de análisis fueron los estados financieros de 2024 y el personal financiero como participantes indirectos. Se abordaron dimensiones clave: estructura patrimonial, ejecución presupuestaria, cumplimiento normativo y eficiencia del gasto. Los hallazgos revelan un aumento en el patrimonio institucional por donaciones y mejores resultados financieros. Sin embargo, se detectó subejecución del 15 % en obras públicas, déficit presupuestario y falencias en el registro y trazabilidad de activos. Se recomienda fortalecer el control interno, mejorar la calidad de la información y planificar mejor el presupuesto. Este estudio aporta a la gestión financiera pública y puede ser base para futuras investigaciones.
Keywords: GESTIÓN FINANCIERA PUBLICA; ESTADOS FINANCIEROS; GAD PARROQUIAL; AUDITORIA GUBERNAMENTAL